2008
DOI: 10.1016/j.energy.2008.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Systematic approach to natural gas usage for domestic heating in urban areas

Abstract: To cite this version:Dejan Brkić, Toma Tanasković. Systematic approach to natural gas usage for domestic heating in urban areas. Energy, 2008, 33 (12) Dear Prof. Lior, We are grateful to referees for their suggestions. According to referees' comments, we have modified our paper "Systematic Approach to Natural Gas Usage for Domestic Heating in Urban Areas"-EGY-D-08-00110R1. We are returning our rewritten manuscript. This paper has not been published previously, it is not under consideration for publication else… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Main reason of such decreased consumption lays in substitution of liquid fuel with natural gas for satisfying of heating demands for households [6]. Oil refineries were mostly destroyed in NATO bombing during 1999.…”
Section: Crude Oilmentioning
confidence: 99%
“…Main reason of such decreased consumption lays in substitution of liquid fuel with natural gas for satisfying of heating demands for households [6]. Oil refineries were mostly destroyed in NATO bombing during 1999.…”
Section: Crude Oilmentioning
confidence: 99%
“…The conclusion showed that HP crucially contributed to the enhancement of system. In general, indirectly and directly gas based systems have been compared in [6] and reached the conclusion that DH is better for small built-up density and skyscrapers.…”
Section: Introductionmentioning
confidence: 99%
“…Its composition varies from field to field and region to region (Table 1). With its various applications, it is domestically used for heating buildings and water, cooking, drying, and lighting (Brkić and Tanasković, 2008;Joelsson and Gustavsson, 2009). Many home appliances running on natural gas include furnaces, barbecues, fireplace logs, pool and spa heaters, and fire pits.…”
Section: Introductionmentioning
confidence: 99%